Impact of Government Expenditure on Education and GDP - Bhattarai, Shom (Journal of Gurubaba, 2024)
This study investigates the impact of government expenditure on education and its relationship with GDP, alongside the effects of school enrollment in secondary education and inflation rates. Grounded in the endogenous growth theory, the study emphasizes the importance of education as a driver of economic growth, particularly in developing nations like Nepal. Using time series data from 1990 to 2020, the research applies a multiple regression model to explore these relationships. The results indicate a significant positive impact of government expenditure on education and school enrollment on GDP, while inflation shows a negative association. The study concludes that increased investment in education leads to substantial economic growth, advocating for policy focus on educational expenditure and inflation management to promote overall development.